A New Approach to the Nuzi Sistership Contract - Freedman, David
former explanations of aḫātūti-contracts were anthropological, based on a fratriarchal society; much simpler is the explanation that girls given to contemporaries were give ana aḫātūti, whereas those given to older men were given ana mārtūti u kallatūti.